2008
DOI: 10.1073/pnas.0804102105
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 1 regulates the phosphorylation state of the polarity scaffold Par-3

Abstract: Phosphorylation of the polarity protein Par-3 by the serine/ threonine kinases aPKC/ and Par-1 (EMK1/MARK2) regulates various aspects of epithelial cell polarity, but little is known about the mechanisms by which these posttranslational modifications are reversed. We find that the serine/threonine protein phosphatase PP1 (predominantly the ␣ isoform) binds Par-3, which localizes to tight junctions in MDCKII cells. PP1␣ can associate with multiple sites on Par-3 while retaining its phosphatase activity. By usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 34 publications
2
62
0
Order By: Relevance
“…A large body of evidence shows that interference in the interactions between TJ proteins perturbs the TJs affecting the barrier permeability of the endothelium ( 38 ). It was further observed that the TJ formation or disintegration depends on the phosphorylation state of TJ proteins (39)(40)(41). However, most of these studies were focused on epithelial TJs, and therefore, the role of phosphorylation of TJ proteins in the preservation or perturbation of endothelial TJ integrity and its barrier function has not been well-studied.…”
Section: Xo-dependent Ros Production Mediates 15(s)-heteinduced Jama mentioning
confidence: 99%
“…A large body of evidence shows that interference in the interactions between TJ proteins perturbs the TJs affecting the barrier permeability of the endothelium ( 38 ). It was further observed that the TJ formation or disintegration depends on the phosphorylation state of TJ proteins (39)(40)(41). However, most of these studies were focused on epithelial TJs, and therefore, the role of phosphorylation of TJ proteins in the preservation or perturbation of endothelial TJ integrity and its barrier function has not been well-studied.…”
Section: Xo-dependent Ros Production Mediates 15(s)-heteinduced Jama mentioning
confidence: 99%
“…The Aurora A phosphorylation site is located close to the Par3-aPKCBC. This region of Par3 contains the binding sites for aPKC, Kif3A, Tiam-1, Stef, Mark2, and Numb (17,18,33,(37)(38)(39)(40)(41). However, preliminary results show that Aurora A phosphorylation does not affect the binding of these proteins.…”
Section: Discussionmentioning
confidence: 61%
“…It has been previously reported that PAR-3 occasionally localizes to the nucleus, as well as to cell-cell contacts (Fang et al, 2007). Biochemical studies indicated that PAR-3 can form a complex with the Ku80, Ku70 and catalytic subunits of DNA-dependent protein kinase (DNA-PK), which are also AP-2-binding proteins (Fang et al, 2007;Nolens et al, 2009;Traweger et al, 2008). Thus, PAR-3 might activate Girdin transcription by binding to the DNA-PK-AP-2 complex, and aPKC might be involved in processes such as protein assembly.…”
Section: Regulation Of Girdin Transcription By the Par-3 Cell Polaritmentioning
confidence: 99%